"They act like they went to hell!": Black teachers, racial justice, and teacher education. Issue 2 (8th July 2021) - Duncan, Kristen E.
Abstract : Purpose: While Black teachers have engaged in racial justice-oriented teaching for centuries and the body of research on racial justice-oriented teachers is growing, very little is known about how teachers come to this work. The purpose of this paper is to focus on where and how Black teachers who teach with racial justice aims learned to engage in this work. Design/methodology/approach: This is a narrative inquiry (Clandinin and Connelly, 2000) study that was designed and analyzed using a critical race theory lens. Findings: Participants learned to engage in racial justice-oriented teaching from their lived experience, particularly from their K-12 teachers who showed why this kind of teaching was necessary. Additionally, participants were highly skeptical of whether or not teacher education programs could prepare White preservice teachers to engage in this kind of teaching. Originality/value: There is very little research focusing on how Black teachers come to engage in racial justice-oriented teaching, and even less that provides insight into how Black teachers perceive teacher education programs at predominantly White institutions (PWIs). This study sheds light on when, where and how Black teachers learn to teach with racial justice aims, and it also illuminates the experiences of Black teachers in PWI teacher education programs.